Discursividades sobre a língua portuguesa na página do FACEBOOK “língua portuguesa”. - Freitas, Luana Vitoria Guimarães (Universidade Federal do Tocantins, 2023)
In this article, we focus on some discourses about the Portuguese language that cross and constitute the “Língua Portuguesa” page available on the Facebook social network. Therefore, we outline the following objectives as lines of action: to analyze some of the representations about “Portuguese Language” circulating on this page; analyze the different knowledge that circulate in the posts on the page and identify the pre-built ones and some of the profiles of internet users. Within the scope of Digital Discourse Analysis, the main axis is circulation, not losing sight of the intertwining with the axes of “constitution” and “formulation”. Under this bias, we focused on posts that had a relevant number of shares and comments, virtual procedures that allow us to focus on the materialization of discourses. We use the historical method for analysis, in which we produce the description-interpretation movement. Based on this method, we relate the materiality of posts and their respective comments to historicity, in order to make the effects of discursive memory work. We turn our gaze to the discourses that the subjects questioned by the ideology produced, allowing contradictory and plural positions to be taken there on the knowledge surrounding the “Portuguese Language”.